FROM SOCIAL MEDIA TO THE DEFENSE FIELD: AN EXPLORATION OF GEN Z'S ROLE IN NATIONAL SECURITY - Sarjito, Aris (Journal of Governance and Public Administration, 2024)
ABSTRACT This research explores the role of Generation Z (Gen Z) in enhancing national security, focusing on their integration into cybersecurity and intelligence roles. As digital natives, Gen Z possesses unique competencies that are crucial for modern security operations. The aim of this study is to analyze these digital skills, including social media proficiency, cybersecurity awareness, and data analysis capabilities, and their application in national defense. Utilizing qualitative research methods with secondary data, such as social media analyses and existing government reports, this study identifies key areas where Gen Z can significantly contribute. Key findings include the critical digital competencies of Gen Z that enhance national security operations, strategies for effectively integrating them into cybersecurity and intelligence roles, and the ethical and practical challenges of their integration. Addressing privacy concerns, misinformation, and the need for ethical guidelines are essential for leveraging Gen Z’s skills while maintaining operational integrity. This research underscores the importance of aligning Gen Z’s capabilities with national security needs and provides recommendations for overcoming integration challenges. Keywords: cybersecurity, digital competencies, Generation Z, intelligence roles, national security